Lectures on Greek Poetry - Schade, Gerson (Wydawnictwo Naukowe UAM, 2016)
The first part of the book is a series of lectures on Greek poetic texts, ranging from the archaic to the pre-Hellenistic age, i.e. from the eighth to the fourth century BC. The main figures as well as their literary setting are discussed. Moreover, important topics determining the literary output are evaluated, too, as, for instance, the opposition between orality and literacy. The second part of the monograph consists of an introduction to Homer’s Iliad. The pervading idea of this part is to show that Homer’s Iliad may well be the work of a single poetic genius, able to include in his work much older and orally conceived parts. This series of lectures provides a selection of classical texts that presents typical examples of Greek poetry. Not only are passages explained and commented on that are relevant to the European poetic tradition, but also a selection of literary analysis and interpretation is provided that may help generally to understand poetic texts. Since literary texts cannot be properly understood without their historical background some basic material of that kind is also constantly provided. Last but not least, broader issues are introduced: how is a text made, and in what way may it reflect the audience’s expectations.

Pierwsza część książki obejmuje zbiór wykładów o poezji greckiej od epoki archaicznej do czasów poprzedzających okres hellenistyczny, czyli od VIII do IV w p.n.e. Przedmiotem rozważań są zarówno główne postacie utworów jak i kontekst literacki, w jakim zostały usytuowane. Ponadto autor podejmuje istotne zagadnienia dotyczące czynników determinujących twórczość literacką, takich jak opozycja pomiędzy oralnością a piśmiennością. Drugą część monografii stanowi wprowadzenie Iliady Homera, ukazanej jako dzieło jednego genialnego poety, który umieścił w nim znacznie starsze, wywodzące się z tradycji oralnej elementy. Zaprezentowany wybór tekstów uwzględnia najbardziej typowe przykłady poezji greckiej. Autor nie tylko objaśnia i komentuje utwory, które zajmują znaczące miejsce w europejskiej tradycji poetyckiej, ale również dokonuje analizy i interpretacji tekstów, ułatwiającej Czytelnikowi ich zrozumienie. Ponadto dostarcza wiedzy na temat kontekstu historycznego, która pozwala na właściwe odczytanie tekstów poetyckich. W książce wprowadzono także szersze zagadnienia dotyczące sposobu tworzenia tekstu oraz realizowania przez twórcę oczekiwań odbiorcy.
Wykłady o poezji greckiej
The series of lectures contained in this volume were written for students at Adam Mickiewicz University. A first group of these lectures are intended to serve as an introduction to Greek poetry of the archaic, classical and pre-Hellenistic age. They treat a selection of texts, ranging from the eighth to the fourth century BC. A second group of these lectures focuses on Homer’s Iliad: while the whole work is treated, the lectures follow the story of Achilles, which is developed mainly in five books. All texts are provided in translation, and secondary literature is discussed and used to make the texts more accessible for young students interested in poetry. The lectures introduce to some of the main issues that characterise the texts, such as their relationship to their primary audience, the impact of orality, and the influence of the eastern poetic tradition on the Greeks. Where appropriate, the lectures also treat the interrelation between various texts, their intertextuality. They try to answer the questions of how poetry did work then, and why these texts do matter for the European poetic tradition.
Keywords: historia kultury greckiej; epika grecka; poezja liryczna; tragedia grecka; "stare" i "nowe" w poezji greckiej; Homer